PENGGUNAAN TOKEN EKONOMI UNTUK MENINGKATKAN PERCAYA DIRI DALAM BERAKTIVITAS DI SEKOLAH - Annisa Fitriana; Giyono Giyono; Ranni Rahmayanthi Z (ALIBKIN (Jurnal Bimbingan Konseling), 2015)
The purpose of this study was to know whether the economy token could improve children's confidence in their activity at school. The research question was